Izzivi in priložnosti tehniškega izobraževanja (University of Maribor Press, 2021)
Challenges and Opportunities of Technical Education. We are living in a time of extremely fast technological development. Robotization, process automation and artificial intelligence are no longer virtual concepts, we are using them in everyday life. Globalization and competitiveness in industry uncompromisingly require new technological solutions, and new challenges and opportunities for education are emerging. That’s why it is so important to explore different approaches that will not only teach students basic skills, but encourage creative thinking and strengthen problem-solving ability. The present monograph was written in a turbulent year of unimaginable changes. The pandemic severely interfered with established ways of working and further accelerated the changes that were indicated by technological developments. The emphasis in the monograph is therefore on technological literacy and the integration of technologies into the educational process. The results of the presented research will be an excellent starting point for all stakeholders in technical education: researchers, teachers, facing technical education challenges, and students, future Technical teachers, who need guidance to seek future technical education opportunities. The articles are based on the final works of the students of the Department of Engineering of the Faculty of Science and Mathematics of the University of Maribor, who highlight important aspects of technical education and offer guidelines for updating the study program.